Evaluating the Adoption Levels of IPM among Vegetable Cultivators in Eastern Uttar Pradesh (Indian Journal of Extension Education, 2025)
This study examines the adoption of Integrated Pest Management (IPM) practices among vegetable growers in Mau District, Uttar Pradesh, during 2022-2023. Two significant blocks, Ratanpura and Kopaganj, were purposively selected, with data collected from 120 respondents across 12 randomly chosen villages. Respondents were categorized into marginal, small, medium, and large growers. Using a semi-structured interview schedule, adoption levels were measured, revealing that 49.16 per cent of respondents had a medium level of IPM adoption. Correlation analysis demonstrated that socio-economic factors, including age, education, landholding, income, risk orientation, and extension contact, had a significant positive relationship with IPM adoption. Conversely, social participation and scientific orientation exhibited significant negative correlations with adoption levels, while marital status and family type had a non-significant positive association. These findings underscore the necessity for policy interventions aimed at overcoming barriers to IPM adoption. Enhancing the accessibility and quality of extension services, implementing targeted training programs to improve awareness, and providing financial incentives and infrastructural support. Promoting sustainable pest management practices not only improves agricultural productivity but also strengthens ecological balance, contributing to long-term agricultural sustainability. These results suggest that increased socio-economic factors are associated with greater IPM adoption among vegetable growers.